A multi-population survey on swine feeding behavior with electronic feeding devices - W. Xin; X. Li; F. Zhang; G. Yan; N. Ding; L. Huang; Z. Zhang (Archives Animal Breeding, 2016)
In this study, we used electronic feeding station observations of pigs to investigate their growth performance and feeding behavior. These pigs were raised in Xinda Livestock Company Ltd. in Henan, China, and followed the Chinese directive for the protection of farm animals. Electronic feeding stations are often used in pig breeding and for identifying loci associated with feed consumption. Moreover, they can also provide much valuable information on pig behavior that could be directly used to improve production efficiency. This study involves three different pig population feeding-intake data from 383 Yorkshire, 243 Landrace and 197 Duroc breeds to investigate their growth performance and feeding behavior. Similar patterns of growth performance (slow–fast–slow) were observed in the three breeds, while the Duroc have a slightly faster average growth rate throughout the whole test period. Study of the number of visits to the feeding station over 24 h detected two peaks of feeding intake activity at 08:00–09:00 and 14:00–15:00. During these two peak feeding times, lower feed intake and less occupation time were observed, implicating fiercer competition at these time periods. The effective intake time for Duroc, Landrace and Yorkshire populations was 19, 16 and 19 min, respectively, suggesting that the ultimate feed intake time for each individual can be set up to 20 min for each visit. Studies on the ADFI (average daily feed intake) showed a significant difference (P value  =  0.000009) between seasons and consistent patterns for these three breeds. The present study provides a detailed survey on pig feed intake behaviors across different populations and feeding seasons.